Association of C1QTNF6 gene polymorphism with risk and clinical features of type 1 diabetes in Chinese: implications for ZnT8A and beta-cell function - Liu, Jinhan; Xia, Ying; Xie, Zhiguo; Li, Xia; Huang, Gan; Hu, Jingyi; Zhou, Zhiguang (Frontiers in Immunology, 2025)
IntroductionGenome-wide association study identified C1QTNF6 as a candidate gene for type 1 diabetes (T1D) in Caucasians. We aimed to investigate if rs229541 in C1QTNF6 conferred susceptibility to T1D in Chinese, independent of DR-DQ genotypes and if this gene polymorphism affected the clinical profiles of T1D.MethodsIn this case–control study, genotypes of C1QTNF6 rs229541 were obtained from 1278 patients with T1D and 1282 nondiabetic controls using MassARRAY.ResultsGenotypic (P = 0.0210) and allelic (P = 0.0084) frequencies were significantly different between the T1D group and the control group. When the model was adjusted for DR-DQ genotypes, G allele carriers were observed less often in the T1D group (P = 0.0423, OR 0.82, 95% CI 0.68-0.99) than in the control group, and the G allele was associated with reduced T1D risk(P = 0.0167, OR 0.83, 95% CI 0.71-0.97). T1D patients who were homozygous for the G allele showed a higher positive rate of ZnT8A than carriers of the A allele (P = 0.0171, OR 1.88, 95% CI 1.12-3.16). By detection of fasting C-peptide, G allele carriers exhibited a lower frequency of beta-cell failure compared to those with A/A genotype (P = 0.0058, OR 0.70, 95% CI 0.54-0.90). C1QTNF6 was not found to be correlated with GADA, IA-2A or age at T1D diagnosis.DiscussionThe polymorphism in C1QTNF6 was independently associated with T1D risk in Chinese and broadly modified clinical features of the disease. This loci might be utilized to construct genetic risk model in combination with the well-known DR-DQ region for future screening of genetically T1D prone individuals among Chinese.